Characterisation and Toxicity Evaluation of Synthesized Phloridzin Chitosan Nanoparticles in in vivo Model - Nambiyar, Aiswarya Gangadheran; Durairaj, Brindha (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Phloridzin, a plant compound is of interest in the field of research due to its antioxidant, anti-inflammatory, anticancer and antidiabetic activity. The current study’s objectives were to create, characterize and evaluate the toxicity of synthesized phloridzin chitosan nanoparticles in Sprague Dawley rats. Materials and Methods The chitosan nanoparticle was synthesized by ionic gelation method. The synthesized nanoparticles were characterized using different techniques like Dynamic Light Scattering, Fourier Transform Infrared Spectroscopy, X-ray Diffraction, Fourier Emission Scanning Electron Microscopy and %Drug Entrapment Efficiency. The toxicity and cellular uptake of phloridzin chitosan nanoparticles were further evaluated by in vitro and in vivo methods. MTT and cellular uptake assay were carried out in SH-SY5Y cells. Following in in vivo Lorke method and the Organization for Economic Co-operation and Development 407, the sub-chronic toxicity of phloridzin chitosan nanoparticles was investigated. Results Chitosan encapsulated phloridzin nanoparticles showed an average particle size of 246.6 d.nm in Dynamic Light Scattering analysis with a polydispersity index of 0.526 and zeta potential of 30.9mv. Fourier Transform Infrared Spectroscopy and X-ray Diffraction analysis confirmed the presence and stability of phloridzin-encapsulated chitosan nanoparticles. In Fourier Emission Scanning Electron Microscopy analysis, the dehydrated sample size was found to be 186 nm. Drug entrapment efficiency was found to be 50.38%. Cell viability range was above 60% after 48 hr incubation. Cellular uptake of nanoparticles was confirmed. The data obtained from the Lorke method indicated that LD50 exceeded 5000 mg/kg. No significant alterations were observed in hematological, biochemical and histopathological studies. Conclusion The findings suggest that the Phloridzin nanoparticles encased in chitosan did not significantly produce toxicity in both in vitro and in vivo.
Keywords: Phloridzin; Chitosan nanoparticle; Toxicity; Liver; Kidney; Brain